Editing the human genome with CRISPR/Cas: a review of its molecular basis, current clinical applications, and bioethical implications - Miguel Ahumada-Ayala; Regina Aguilar-López; Nicolai González-Stoylov; Esmeralda Palacio-Sosa; David E. Cervantes-Barragán; Liliana Fernández-Hernández (Permanyer, 2023)
CRISPR/Cas genes evolved in prokaryotic organisms as a mechanism of defense designed to identify and destroy genetic material from threatening viruses. A breakthrough discovery is that CRISPR/Cas system can be used in eukaryotic cells to edit almost any desired gene. This comprehensive review addresses the most relevant work in the CRISPR/Cas field, including its history, molecular biology, gene editing capability, ongoing clinical trials, and bioethics. Although the science involved is complex, we intended to describe it in a concise manner that could be of interest to diverse readers, including anyone dedicated to the treatment of patients who could potentially benefit from gene editing, molecular biologists, and bioethicists. CRISPR/Cas has the potential to correct inherited diseases caused by single point mutations, to knock-in the promoter of a gene whose expression is highly desirable or knockout the gene coding for a deleterious protein. CRISPR/Cas technique can also be used to edit ex vivo immune cells and reinsert them in patients, improving their efficiency in attacking malignant cells, limiting the infectious potential of viruses or modulating xenotransplant rejection. Very important bioethical considerations on this topic include the need to internationally regulate its use by ad hoc expert committees and to limit its use until safety and bioethical issues are satisfactorily resolved.